2019
DOI: 10.31744/einstein_journal/2019rw4320
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence following subtotal and total hysterectomy: a systematic review

Abstract: Objective: To evaluate the best surgical approach for the female urinary incontinence. Methods: Systematic review conducted in MEDLINE ® Cochrane, EMBASE and LILACS database up to September 1 st , 2017. Articles were selected according to study type, type of intervention and outcomes. Articles were selected by more than one researcher based on title, abstract and full text. The SIGN checklist was used for bias assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Altman et al, in a cohort study, found no correlation between the incidence of UI and the type of hysterectomy [27]. However, a systematic review by Longo et al revealed a higher frequency of UI after subtotal hysterectomy compared to total hysterectomy [28]. Moreover, the patient's satisfaction with the surgery and impact of hysterectomy on UI is strongly connected to other factors, such as the number of vaginal deliveries, being overweight, and daily urge symptoms without incontinence prior to the operation-which has a negative influence on the rate of remission of UI after hysterectomy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Altman et al, in a cohort study, found no correlation between the incidence of UI and the type of hysterectomy [27]. However, a systematic review by Longo et al revealed a higher frequency of UI after subtotal hysterectomy compared to total hysterectomy [28]. Moreover, the patient's satisfaction with the surgery and impact of hysterectomy on UI is strongly connected to other factors, such as the number of vaginal deliveries, being overweight, and daily urge symptoms without incontinence prior to the operation-which has a negative influence on the rate of remission of UI after hysterectomy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Working with individuals to reduce modifiable risk factors may improve continence. [5][6][7][8][9][10]…”
Section: Abstract: Urinary Incontinence Urinary Incontinence Evaluati...mentioning
confidence: 99%
“…Para el tratamiento de la IU no neurogénica y en hombres tras prostatectomía retropúbica radical, se muestra como una opción fiable, eficiente, satisfactoria y segura, el esfínter artificial; ya que se produce una mejoría tanto de la calidad de vida, como del mantenimiento del flujo urinario evitando pérdidas de orina y síntomas obstructivos derivados de la intervención. El nivel de satisfacción de esta técnica se ve incrementado con características del paciente tales como la juventud y el alto nivel de actividad física [21][22][23][24][25] .…”
Section: Autor Autorunclassified